Polymethacrylate Coated Electrospun PHB Fibers as a Functionalized Platform for Bio-Diagnostics: Confirmation Analysis on the Presence of Immobilized IgG Antibodies against Dengue Virus - Hosseini, S.; Azari, Pedram; Jiménez-Moreno, M.F.; Rodriguez-Garcia, A.; Pingguan-Murphy, Belinda; Madou, M.J.; Martinez-Chapa, S.O. (MDPI, 2017)
In this article, a combination of far field electrospinning (FFES) and free-radical polymerization has been used to create a unique platform for protein immobilization via the physical attachment of biomolecules to the surface of the fiber mats. The large specific surface area of the fibers with its tailored chemistry provides a desirable platform for effective analyte-surface interaction. The detailed analysis of protein immobilization on a newly developed bio-receptive surface plays a vital role to gauge its advantages in bio-diagnostic applications. We relied on scanning electron microscopy (SEM), diameter range analysis, and X-ray photoelectron spectroscopy (XPS), along with thermal gravimetric analysis (TGA), water-in-air contact angle analysis (WCA), Fourier transform infrared spectroscopy (FTIR), and atomic force microscopy (AFM) to study our developed platforms and to provide valuable information regarding the presence of biomolecular entities on the surface. Detailed analyses of the fiber mats before and after antibody immobilization have shown obvious changes on the surface of the bioreceptive surface including: (i) an additional peak corresponding to the presence of an antibody in TGA analysis; (ii) extra FTIR peaks corresponding to the presence of antibodies on the coated fiber platforms; and (iii) a clear alteration in surface roughness recorded by AFM analysis. Confirmation analyses on protein immobilization are of great importance as they underlay substantial grounds for various biosensing applications.